New model of work of the gas-turbine engine - Дихановський, В.М. (Proceedings of National Aviation University (archive), 2004)
Problem questions of the gas-turbine engines exploitation are analysed. It is shown, that the gas-mechanics regulation of aerodynamic profile attack corner theorem allowed to design the regulation of the axial compressor system. This system is ability to provide reliable functioning of the gas-turbine engine at any service conditions.